Challenges and Opportunities for the Encapsulation of Enzymes over Porous Solids for Biodiesel Production and Cellulose Valorization into Glucose - Cirujano, Francisco G.; Dhakshinamoorthy, Amarajothi (ChemCatChem, 2021)
Different porous supports of enzyme catalysts are reviewed here for the valorization of biomass and production of biodiesel, given the high yields and mild reaction conditions in the presence of the biocatalysts. Two main types of enzymes have been widely employed for such endeavors, i. e. lipase and cellulase, which are able to produce fatty acid alkyl esters and glucose from fats and cellulose, respectively. Robust and versatile porous silica, carbon, polymers and metal‐organic frameworks are among the most employed supports of the enzymes, via simple adsorption or covalent grafting. Herein, we provide a comprehensive review by comparing the catalytic performance of the enzymes supported over porous solids with respect to the bulk/free enzymes in terms of yields, stability and recycling, highlighting the benefits of the porous support for an optimal biocatalytic performance in the biodiesel production and cellulose valorization into glucose. The final section provides our views for further developments in this field. Encapsulation: This minireview provides an overview on various strategies employed in the encapsulation of enzymes over porous solids. Particularly, the positive benefits of porous supports in enhancing the catalytic performance and the stability of the encapsulated enzymes compared to their respective free enzymes are highlighted with appropriate examples. Our views for future works are also summarized.